Pengaruh IPM, PDRB dan Pengeluaran Pemerintah Terhadap Kemiskinan di Jawa Tengah dengan Zakat Sebagai Moderating - Mohammad Soleh; Nunung Wahyuni (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2021)
This research is motivated by the number of poverty in Central Java Province which is still high, which is in second place from all provinces in Indonesia. The purpose of this study was to determine the effect of the human development index, gross regional domestic product, and government spending on poverty in Central Java Province with zakat as a variable moderating. This research is quantitative research with an emphasis on data analysis in the form of numbers and processed using statistical methods. The research population is in districts/cities in Central Java, with sampling using the purposive sampling method. The technique of collecting data is through indirect observation using methods of internet research and library research. The research instrument used stationarity test, classical assumption test, panel data regression test, and hypothesis testing. Analysis tool using Eviews 9 with selected regression analysis model Random effect. The results showed that the human development index had a significant negative effect on poverty, GRDP had an insignificant positive effect on poverty, and government spending had a significant positive effect on poverty. Meanwhile, zakat funds are not able to moderate the human development index and GRDP towards poverty, and zakat funds are able to moderate government spending on poverty.